Use of maternity open days initiative to increase access to comprehensive maternal and neonatal health services at the Lwala Community Health Centre (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Maternity open day (MOD) is an event in which a health facility opens its doors to the community and provides a specific opportunity for pregnant women and their birth companions to interact freely with health care providers and receive antenatal care services, including obstetric ultrasound, and tour maternity units.   Objective: To increase access and utilization of MNH services, improve knowledge, promote transparency, familiarize with the environment, procedures, and maternity staff, and increase the client's knowledge and confidence on what to expect during labor and delivery.Results: It ensured an increase in the number of women seeking comprehensive antenatal care (ANC), including ANC profile care at both first and fourth ANC visits, and skilled birth attendants. The (MODs) provided a platform to expand access to affordable maternity care through client enrollment in Linda Mama services. Over 99% of pregnant women who attended MODs embraced hospital deliveries and 99% skilled births. A total of 1060 women attended MOD, and 3,903 women underwent obstetric ultrasound, with zero maternal deaths and one neonatal death recorded between 2022 and 2023.Conclusion: Maternity open day provides a platform for increasing access to comprehensive antenatal care and affordable maternity care through Linda Mama. It improved the quality of maternal and child health services, reduced defaulters in the ANC clinics, and increased access to MNH services for continuum care and built trust between women and healthcare providers.